Incidental findings of suspect multiple odontomas and impacted supernumerary teeth on panoramic radiograph: a case report - Munasyifa, Tazkia; Pramanik, Farina (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: This case report aimed to describe radiographic features of suspect multiple odontomas in an incidental case. Case Report: A 32-year-old man non syndromic patient was referred to the Dental Radiology Unit of RSGM Unpad for panoramic examination. He was complaining about a pain in lower mandible and was clinically diagnosed with an impacted 48. Radiographic findings appeared irregular radiopaque with radiodensity that resembles enamel and dentin, surrounded by a thin radiolucent capsule in the left and right regions body of the mandible. Additionally, there is radiopaque that resembles a para premolar supernumerary tooth, inferior from the lesion to the mandibular cortical bone. Conclusion: In this case, irregular radiopaque areas with radiodensity that resembles enamel and dentin, surrounded by thin radiolucent capsules, were found as the radiographic features that led the radiodiagnosis of odontomas.